Bosnia and Herzegovina and Bosnians (1918-1921) – in between of making peace and violence - Bećirović, Denis (Historical Thought, 2025)
This paper deals with the basic characteristics and opportunities in Europe and Bosnia and Herzegovina during the first two years after the end of the First World War. There were major political upheavals in these years, the emergence of new states, conflicts of different concepts and ideologies. Bosnia and Herzegovina was openly confronted for the first time with Yugoslav monarchist centralism and the Greater Serbia national programme. The paper also discusses the position of Bosniaks in Bosnia and Herzegovina, who were continuously subjected to robberies, persecutions and murders, during the years immediately following the First World War